Prestress Loss Law of Anchor Cables and Deformation Control for Metro Station Deep Foundation Pit in Soil-rock Composite Strata - SUN Chao; XIN Qingfei; SUN Zhicheng; WU Yufei; ZHOU Hao; XU Dongming; YANG Enze (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] To control construction risks associated with deep metro station foundation pit in soil-rock composite strata, it is essential to analyze the stress characteristics of anchor cables and excavation-induced deformation during construction, formulate appropriate control measures accordingly, and verify their effectiveness on-site. [Method] Taking the deep foundation pit project construction at a metro station in Qingdao as a case study, non-destructive testing methods are employed to obtain the short- and long-term evolution law of anchor cable prestress. A 3D foundation pit–stratum model is developed using FLAC3D software to analyze the displacement of the retaining piles and the distribution characteristics of plastic zones under prestress loss conditions. The rationality of the support measures is verified based on pile displacement and steel strut axile force. [Result & Conclusion] Non-destructive testing results show that over 75% of the anchor cables passed the initial tensioning acceptance criteria. However, within 5 days, the prestress loss exceeded 10% of the lock-in value, indicating a relatively high level of short-term prestress loss. After the occurrence of prestress loss, the final horizontal displacement of the excavation is 2.5 times of the design value, with a maximum displacement of 35.4 mm, consistent with field monitoring results. Under conditions of low anchor cable prestress, wide and extensive plastic zones developed on both sides of the foundation pit, increasing the likelihood of the surrounding rock deformation. The installed steel struts shared part of the active earth pressure and altered the horizontal displacement distribution of the retaining piles. Following their deployment, the steel strut axile force initially increased, then gradually decreased, and eventually stabilized. The reinforcement measures of adding steel struts effectively controlled the deformation of the surrounding rock.